2020
DOI: 10.1111/ddi.13128
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the usefulness of citizen science data for habitat suitability modelling: Opportunistic reporting versus sampling based on a systematic protocol

Abstract: Aim To evaluate the potential of models based on opportunistic reporting (OR) compared to models based on data from a systematic protocol (SP) for modelling species distributions. We compared model performance for eight forest bird species with contrasting spatial distributions, habitat requirements and rarity. Differences in the reporting of species were also assessed. Finally, we tested potential improvement of models when inferring high‐quality absences from OR based on questionnaires sent to observers. Loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 76 publications
1
22
0
1
Order By: Relevance
“…Even if the AUC values alone might not be the best model performance indicator (Lobo et al, 2008), all selected models ranged between 0.7 and 0.9, which, together with the low omission rate values, indicates good overall predictive performance. This reinforces the potential of opportunistically collected datasets to produce reliable estimates of habitat suitability, as Henckel et al (2020) found recently.…”
Section: Discussionsupporting
confidence: 86%
“…Even if the AUC values alone might not be the best model performance indicator (Lobo et al, 2008), all selected models ranged between 0.7 and 0.9, which, together with the low omission rate values, indicates good overall predictive performance. This reinforces the potential of opportunistically collected datasets to produce reliable estimates of habitat suitability, as Henckel et al (2020) found recently.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, a study of bugs and beetles found that smaller species are typically less represented in citizen science data 68 . Importantly, because this body size bias is systematic, it may be easier to model, as we know that these data are not missing at random (e.g., 70 ) and thus body size can be included in various modelling processes when using unstructured citizen science data (e.g., 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our goal was to examine potential range shifts in regions pertinent to possible hybridization, and perhaps a cautious approach is to interpret our results as predictions confined to a subset of the geographical range. Citizen science data may be particularly prone to opportunistic collection, and hence, biased occurrence data (Syfert et al, 2013;Tiago et al, 2017 (Henckel et al, 2020). In the present study, the contributions of citizen science data were limited to only three data points retained in any of the model; the subset of the observations that temporally overlapped with the available environmental data happened to be comprised mostly of museum data.…”
Section: Discussionmentioning
confidence: 95%